Ideal food pyramid for patients with rheumatoid arthritis: A narrative review. Issue 3 (March 2021) - Rondanelli, Mariangela; Perdoni, Federica; Peroni, Gabriella; Caporali, Roberto; Gasparri, Clara; Riva, Antonella; Petrangolini, Giovanna; Faliva, Milena Anna; Infantino, Vittoria; Naso, Maurizio; Perna, Simone; Rigon, Chiara
Summary: Emerging literature suggests that diet plays an important modulatory role in rheumatoid arthritis (RA) because diet is an environmental factor that affects inflammation, antigen presentation, antioxidant defense mechanisms and gut microbiota. Patients with RA frequently ask their doctors about which diets to follow, and even in the absence of advice from their physicians, many patients are undertaking various dietary interventions. Given this background, the aim of this review is to evaluate the evidence to date regarding the ideal dietary approach for management of RA in order to reduce the counteracting inflammation, and to construct a food pyramid for patients with RA. The pyramid shows that carbohydrates should be consumed every day (3 portions of whole grains, preferably gluten free), together with fruits and vegetables (5 portions; among which fruit, berries and citrus fruit are to be preferred, and among the vegetables, green leafy ones.), light yogurt (125 ml), skim milk (200 ml), 1 glass (125 ml) of wine and extra virgin olive oil; weekly, fish (3 portions), white meat (3 portions), legumes (2 portions) eggs (2 portions), seasoned cheeses (2 portions), and red or processed meats (once a week). At the top of the pyramid, there are two pennants: one green means that subjects with RA need some personalized supplementation (vitamin D and omega 3) and one red means that there are some foods that are banned (salt and sugar). The food pyramid allows patients to easily figure out what to eat.